Criminal charges in marriage from the perspective of positive law in Indonesia - Anizar Anizar (Tunas Institute, 2023)
Charges of violating family law are one form of reform of marriage law that was never previously regulated. Muslim countries have different legal provisions against charges for violations of this family law. This research uses the literature method and normative juridical approach by examining library data as the source. Primary data sources used in this research are books, laws, court decisions, legal theories and opinions of jurists related to family law charges, and previous studies such as relevant research. This research aims to determine the legal provisions regarding charges for family law violations. The results of the discussion and research explain that not all countries have legal provisions regarding charges in violation of this family law, and the legal provisions regarding these charges vary from one country to another. In general, the legal charges are related to violations of various issues surrounding marriage, such as underage marriage, forced marriage, prevention of marriage permitted by sharia law, prohibited marriage, marriage registration, out-of-court marriage, dowry, marriage expenses, polygamy, divorce, maintenance, treatment of wives, women’s rights after divorce, and inheritance rights from spouses and families.